1987
DOI: 10.1136/hrt.58.4.339
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bepridil with amiodarone in the treatment of established atrial fibrillation.

Abstract: Fourteen patients with established atrial fibrillation (longer than three months) that was refractory to treatment were studied to compare the clinical and electrophysiological effects of amiodarone and bepridil. All patients initially received bepridil for three weeks (200-600 mg/day), followed by amiodarone for two to three months (100-400 mg/day). Bepridil seemed to be slightly more effective than amiodarone in converting the fibrillation to sinus rhythm (nine of fourteen compared with four of ten). The ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 4 publications
2
34
2
Order By: Relevance
“…The first trial with the drug for AF was reported in comparison with amiodarone. 19 In this study, bepridil was used at a high dose of 400-600 mg/day for persistent AF, and the effects were compared to those produced by amiodarone, which was started at 800 mg/day and thereafter reduced to 200 mg/day. Nine of 14 patients were converted to sinus rhythm by the use of bepridil, while 4 of 10 were converted by amiodarone.…”
Section: Early Studies With Bepridilmentioning
confidence: 99%
See 2 more Smart Citations
“…The first trial with the drug for AF was reported in comparison with amiodarone. 19 In this study, bepridil was used at a high dose of 400-600 mg/day for persistent AF, and the effects were compared to those produced by amiodarone, which was started at 800 mg/day and thereafter reduced to 200 mg/day. Nine of 14 patients were converted to sinus rhythm by the use of bepridil, while 4 of 10 were converted by amiodarone.…”
Section: Early Studies With Bepridilmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] In foreign countries, the antiarrhythmic effects of the drug were first examined based upon the experimental results in 1986. 19 Although bepridil at a high dose of 600 mg/day was effective for converting AF to sinus rhythm, it frequently caused remarkable QT prolongation and life-threatening arrhythmias including torsades de pointes. 19 The results estimated increased risks compared with the benefits, and therefore, the drug could not be used for AF treatment in the USA and Europe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, bepridil (200-600 mg/day) was associated with the development of serious ventricular arrhythmias caused by excessive prolongation of the QT interval. 23 In the present study, however, the dosage of bepridil was 200 mg/day and serum K ≥3.8 mmol/L was maintained by administration of either an angiotensin-converting enzyme inhibitor or spironolactone to avoid the proarrhythmic effects of bepridil.…”
Section: Electrophysiology Of Bepridil and Aprindinementioning
confidence: 99%
“…In Western countries, where the maximum dosage of bepridil (600 mg/day) used was significantly higher in clinical practice, TdP was frequently reported. Therefore, bepridil was branded as a drug with dangerous side effects and taken off the market despite its superior anti-arrhythmic actions 12) . Bepridil is still available in Japan at an appropriately lower dose (100-200 mg/day) and the evidence regarding efficacy and adverse effects, including TdP, has accumulated.…”
Section: Adverse Effects Of Bepridilmentioning
confidence: 99%